A Threshold Effect of Financial Development on Natural Resource Rents-Sustainable Human Development Nexus: Empirical Evidence from Sub-Saharan Africa - Bani, Yasmin; Gutale, Ali Abdulkadir Ali; Abdul-Rahim, Abdul Samad; Afandi, Syamsul Herman Mohammad (International Journal of Energy Economics and Policy, 2024)
Sub-Saharan African (SSA) nations are falling behind in human development when compared to other regions globally, despite their abundant natural resources. Several Sub-Saharan African states have an underdeveloped financial structure, leading to underutilization of natural resource profits for human development. This research examines how the level of financial development impacts the relationship between natural resource rents and sustainable human development in 40 SSA countries from 2005 to 2019. This research used the dynamic panel threshold (DPT) approach, an advanced econometric methodology designed to address concerns often seen in panel data such as endogeneity, cross-sectional dependence, and heterogeneity. The cointegration findings showed a long-term association among the variables. The dynamic panel threshold analysis showed that natural resource rent had a detrimental influence on human capital development when financial development was below a certain threshold. Conversely, the outcomes were different when financial development exceeded the threshold. Financial system progress in Sub-Saharan African states considerably uses resource windfalls to improve sustainable human development. This research conducted robustness tests by using alternative estimates excluding outlier sample countries and extra proxies. The conclusions remained unchanged. Policy suggestions were introduced to enhance the financial sector and improve institutional quality in order to ensure sustainable growth in the SSA area.